THE FIELD OF NATIONAL AND RELIGIOUS VALUES IN THE CONTEXT OF SPIRITUAL AND CULTURAL GLOBALIZATION - Abuov Amrekul (Scientific Journal of Pedagogy and Economics, 2020)
One of the powerful factors shaping the image of the nation is religion. Religion defines the basic ethical norms, as well as the system of relations within and outside the ethnic community. The specifics of religion will to some extent determine the development of national culture and stimulate or limit the development of certain genres of art. The national character and the ethical nature of the nation are largely related to the national religion. One of the most important foundations in the life and development of a nation is language. Language reflects the whole history, culture, value system and worldview of the people. The environment, religion and language all work together to create ethnic psychology. Ethnic psychology shapes the thinking, behavior and actions of members of a particular ethnic community, the whole way of life, in short, the image of the world. Parents pass it on to the next generation, and society supports it with its socio-ethical system.